Management of uterine prolapse during pregnancy with vaginal pessary: Case report - Güngör, Sami; Kumbak Aygün, Banu; Özkan, Zehra Sema; Şimşek, Mehmet (My University, 2012)
Uterine prolapse, commonly seen in women beyond childbearing age, has been reported rarely during pregnancy. Significant complications may develop in some cases. Preterm labor, fetal loss, recurrent urinary tract infections and acute urinary retention are major complications. In order to avoid possible maternal and fetal risks, early recognition and close follow-up are essential. Management of the pregnancy, labor and delivery in women with uterine prolapse varied considerably. Treatment approach depends on the gestational week, severity of the condition, associated complications and the patient's preference. This paper reports the management of uterine prolapse with vaginal pessary in a 14 weeks' pregnant woman hospitalized with the complaint of acute urinary retention and her successful normal vaginal delivery. Vaginal pessary with appropriate patient training can be effectively used in the management of uterine prolapse diagnosed during pregnancy. Copyright © 2012 by Türkiye Klinikleri.
Gebelikte uterus prolapsusunun vajinal pesser ile yönetimi
Keywords: Pregnancy; Uterine prolapse; Vaginal pessary